Remission of relapsed/refractory classical Hodgkin lymphoma induced by brentuximab vedotin and pembrolizumab combination after allogeneic hematopoietic stem cell transplantation: a case report - Giannotti, Federica; De Ramon Ortiz, Carmen; Simonetta, Federico; Morin, Sarah; Bernardi, Chiara; Masouridi-Levrat, Stavroula; Chalandon, Yves; Mamez, Anne-Claire (Frontiers in Immunology, 2024)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potentially curative treatment option for patients with highly chemorefractory Hodgkin lymphoma (HL). The CD30-targeting antibody drug conjugate Brentuximab-Vedotin (BV) and programmed cell death protein-1 (PD-1) blocking agents have demonstrated clinical activity with durable responses in relapsed/refractory (r/r) HL. However, patients with a history of allo-HSCT were frequently excluded from clinical trials due to concerns for the risk of graft-versus-host disease (GVHD). We report the clinical history of a patient with refractory classical HL who underwent two allo-HSCT (first from matched unrelated and second from haploidentical donor) after relapsing on BV and on nivolumab, and for whom durable remission was finally obtained using BV-pembrolizumab combination for relapse after haploidentical HSCT. Such treatment was associated with the onset of GVHD after only 2 cycles which led to treatment discontinuation. However, the side effects were rapidly controlled and, after two years of follow-up, the patient is still in remission. Our data support the feasibility and efficacy of combining PD-1 blockade with BV to enhance the graft-versus-lymphoma effect after allo-HSCT.